Discourses of Empowerment in Edward II: (Homo) Erotic and Political Desires - Acón Chan, Lai Sai (2009)
This article's focus is how desire gives way to particular forms of empowerment in Christopher Marlowe's play Edward II. During a historical period when "abnormal" sexual practices (as Michel Foucault would ironically call them in The History of Sexuality) such as homosexuality and female desire circulated in society but were not yet labeled as such, Marlowe composes a brilliant piece about discourses that are precisely uprooted in needs or desires that are the very core of humanity.